Trends in hospitalizations and emergency department visits among women with hyperglycemia in pregnancy between 2008 and 2017 in Taiwan - Wang, Jun-Sing; Chin, Ming-Chu; Chen, Jung-Fu; Huang, Chien-Ning; Hwu, Chii-Min; Ou, Horng-Yih; Yang, Yi-Sun; Hsu, Chih-Cheng; Wang, Chih-Yuan (Frontiers in Endocrinology, 2022)
We investigated health service utilization, including hospitalizations and emergency department visits, for women with hyperglycemia in pregnancy between 2008 and 2017 in Taiwan. Data from the Health and Welfare Data Science Center were used to conduct this nationwide population-based study. We identified pregnant women and the date of childbirth according to Birth Certificate Applications from 2007 to 2018. The study population was divided into four groups: known DM, newly diagnosed DM, GDM, and no DM/GDM. To assess quality of healthcare during the gestation period, trends in 30-day readmission rate, number of emergency department visits/hospitalizations per 100 childbirths, and length of hospital stay from 2008 to 2017 were examined. A total of 1830511 childbirths and 990569 hospitalizations were identified for analyses. Between 2008 and 2017, women with hyperglycemia in pregnancy (known DM, newly diagnosed DM, and GDM) had a higher rate of hospitalization, a longer length of hospital stay, and higher rates of various maternal and fetal outcomes, compared with women with no DM/GDM. Nevertheless, the differences between women with GDM and those with no DM/GDM in the aforementioned outcome measures were modest. Women with GDM had a modest decrease in the 30-day readmission rate (p for trend 0.046) with no significant difference in the number of emergency department visits during the study period. Our findings provide evidence of the quality of healthcare for women with GDM between 2008 and 2017 in Taiwan.